Crystal structure of poly[[diaquatetra-μ2-cyanido-platinum(II)iron(II)] methanol 4/3-solvate]: a three-dimensional Hofmann clathrate analogue - Volodymyr M. Hiiuk; Vasyl Mykhailovych; Sergiu Shova; Irina A. Golenya; Il'ya A. Gural'skiy (Acta Crystallographica Section E: Crystallographic Communications, 2022)
In the title polymeric coordination compound, {[FePt(CN)4(H2O)2]·1.33CH3OH}n, the FeII cation (site symmetry 4/mm.m) is coordinated by the N atoms of four cyanide anions (CN−) and the O atoms of two water molecules, forming a nearly regular [FeN4O2] octahedron. According the Fe—N and Fe—O bond lengths, the FeII atom is in the high-spin state. The cyanide anions act in a bridging manner to connect the FeII and PtII atoms. The [Pt(CN)4]2– moieties (Pt with site symmetry 4/mm.m) have a perfect square-planar shape. The latter anion is located perpendicular to the FeN4 plane, thus ensuring the creation of a three-dimensional framework. The crystal structure features methanol solvent molecules of which 4/3 were located per FeII cation. These solvent molecules are located in hexagonal pores; they interact with coordinating water molecules through weak hydrogen bonds. Other guest molecules could not be modelled in a satisfactory way and their contribution to the scattering was removed by a mask procedure.